Formation of the border guard on the russian-persian border in the late XIX – early XX century - Konstantin A. Pavlov (Кавказология)
The article analyzes the process of development of protecting the Russian-Persian border-by-border guard units in the late XIX–early XX century. Properly organized and precisely established border surveillance, forming the conditions for protecting the state border, was important in ensuring security on the borders of the Caucasus in the XIX century. This was because the state border in the Caucasus was violated not only by professional smugglers but also by the local population. The article shows that, because of these circumstances, the establishment of expedient border surveillance on the Russian-Persian border, together with a thorough study of local geographical, topographic and economic conditions, was the subject of the first state's importance. Based on the studied sources and literature, the process of the border guard formation on the Russian-Persian border was revealed. In pre-revolutionary and Soviet historiography, studies of the activities of border units were practically not performed, and only in the post-Soviet period, interest was shown in this issue. However, the works of the post-Soviet period are mainly overview and did not concern the issues of the history of the formation of the border guard on the Russian–Persian border in the late XIX–early XX centuries. The paper shows that without specialized units, the Russian Empire could not protect its national interests in the border area in the Caucasus. The development of the system of protection of the Russian-Persian border was conducted under difficult topographic conditions.